Impact of oral hygiene training to Anganwadi and Accredited Social Health Activist workers on oral health of young children in tribal regions of Rajasthan State, India - Suhani Rakesh Khanna; Dinesh Rao; Sunil Panwar; Safna Ameen (Wolters Kluwer Medknow Publications, 2021)
Context: Early childhood caries is one of the most widespread diseases affecting children in urban and rural India. Community health workers can bring about a quantum of change in improving the oral health in children. Aims: The aim of the study was to assess the impact of oral health training imparted to Anganwadi and accredited social health activist (ASHA) workers on improving the oral hygiene of 148 children aged 1-6 years. Settings and Design: The preintervention followed by oral health training and postintervention assessment were done at three Anganwadi and ASHA centers of Rajasthan. Methodology: The preintervention data included Decayed, Missing, and Filled Teeth/decayed, extracted, and filled teeth, oral hygiene indices (Oral Hygiene Index-Simplified [OHI-S] and Oral Hygiene Index Simplified-Modified [OHIS-M]), plaque index, and caries activity using Oratest. The oral health training consisted of PowerPoint presentations, video presentations, live demonstrations on brushing technique, rinsing, plaque disclosure, and flossing technique. They were enlightened on deleterious oral habits, emergency protocol on trauma, etc. The postintervention data included outcome measures consisting of oral hygiene indices (OHI-S and OHIS-M), plaque index, and Oratest after 2 months to evaluate the impact of training. Statistical Analysis used: The data were analyzed using Chi-square test, Fisher's exact test, independent t-test, paired t-test, and one-way analysis of variance test. Results: There was a significant improvement in toothbrushing practices and rinsing (P < 0.05). There was a significant difference in debris index, calculus index, OHI-S/OHIS-M, plaque index, and Oratest after intervention (P < 0.05). Conclusion: Empowering Anganwadi and ASHA workers can be a feasible approach in India, where oral health is not a priority in primary health care as yet.